N-Acetylcysteine increases glutathione levels in experimental models of heart diseases: a systematic review and meta-analysis - Ferreira, Aimée Souto; Schaan, Thomas; Casagrande, Guilherme Curi Aiub; Rohde, Luis Eduardo; Andrades, Michael (Clinical and Biomedical Research, 2026)
Introduction: Cardiovascular diseases (CVD) are the leading cause of death worldwide, with oxidative stress playing a significant role in their progression. The use of N-acetylcysteine (NAC), a well-known antioxidant and a precursor to glutathione (GSH), has shown potential in preventing different types of CVD. Yet, there are limited data assessing NAC’s impact on GSH levels in animal models of CVD. Objective: To estimate the effects of NAC supplementation on reduced glutathione (GSH) and total glutathione levels in cardiac tissue or serum/plasma from animals with established heart disease. Methods: We searched PubMed, Embase, Web of Science, Scielo, Lilacs/BINACIS, MedRxiv, and BioRxiv databases (the search was completed in February 2025). We included studies in animal models (of any species) of CVD receiving NAC (via any route or dose) and performed a random-effects meta-analysis and Risk of Bias assessment (PROSPERO register: CRD42023382024). Results: We identified 738 articles, fully reviewed 48, and included 8 in the meta-analysis. Meta-analysis showed that NAC supplementation resulted in a statistically significant increase in GSH (SMD = 1.54, CI 95% = 0.13–2.94; p = 0.03), with high heterogeneity (I² = 88%) and in total glutathione (SMD = 1.22, CI 95% = 0.41–2.02; p = 0.003) with moderate heterogeneity (I² = 49%). Subgroup analyses suggested a dose-dependent effect, while sensitivity analyses indicated that species- and model-related differences influenced the magnitude of the GSH response. Conclusion: NAC supplementation increases glutathione levels in animal models of heart disease, although the magnitude of the effect appears dose- and model-dependent.